Penerapan Etika Jurnalistik Pada Produksi Videografi Kompas Tv Riau - Ardesaputra, Aditya Aviciena; ., Defhany (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This research focuses on the lack of application of the journalistic code of ethics at Kompas TV Riau, especially on the YouTube platform. The goal is to analyze the implementation of the code of ethics in the practice of journalists. The benefits include theoretical, practical, and academic contributions in understanding journalistic ethics at Kompas TV Riau as well as a reference for future research.The research used descriptive qualitative methods with the location at Kompas TV Riau Office. Informants were selected through purposive sampling. Data were collected through interviews, observation, and literature study. Data analysis used Miles and Huberman techniques. Data validity was verified through source triangulation to ensure its validity and reliability.Based on interviews with Kompas TV Riau informants, the station applies the motto "Independent and Trustworthy" consistently in journalistic tasks. This commitment is reflected in all aspects of the work, from the selection of sources to the editing process. The importance of complying with the journalistic code of ethics emphasizes awareness of social responsibility and moral principles in presenting accurate and objective information.This research successfully evaluated Journalistic Ethics towards Visual Communication Videography at Kompas TV Pekanbaru. Interviews with the editor-in-chief, coordinators, reporters, and editors showed a commitment to independence and accuracy of information. Kompas TV Riau complies with the journalistic code of ethics, maintains integrity, and builds public trust in the information conveyed through visual videography communication.